The Impact of Human Capital and Social Capital on the Recognition of Entrepreneurial Opportunities for Women SMEs Entrepreneurs in Medan - Inneke Qamariah; Yasmin Chairunisa Muchtar (AIBPM Publisher, 2021)
With the transformation of the industrial economy into a science-based economy, the notion of assets has altered. Intellectual capital is the foundation of a science-based economy. Intellectual capital may also be defined as a management technique utilized by a company to produce money and accomplish results. To accomplish the success of women entrepreneurs in the city of Medan, business actors may use resources such as human capital, and business actors can hire competent and knowledgeable workers to boost the company's performance. Social capital is a rich source of knowledge that helps individuals to find various goal combinations while developing a new product or service for a specific market. This study's population consists of MSME Women Entrepreneurs in Medan City. The study sample consisted of 62 persons who were registered with the Medan City Trade Office. Multiple Linear Regression is a data analysis approach. The goal of this study was to examine the impact of Human Capital and Social Capital on Entrepreneurial Opportunity Recognition of Medan City's Women MSME Entrepreneurs. Keyword: Intellectual Capital, Human Capital, Social Capital, Entrepreneurial Opportunity Recognition, Woman Entrepreneurs, SMEs